Clinical Outcomes Associated With His-Purkinje System Pacing vs. Biventricular Pacing, in Cardiac Resynchronization Therapy: A Meta-Analysis - Gui, Yang; Ye, Lifang; Wu, Liuyang; Mai, Haohui; Yan, Qiqi; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2022)
Aims: His-Purkinje system pacing has recently emerged as an alternative to biventricular pacing (BIVP) in cardiac resynchronization therapy (CRT). The aim of this study was to conduct a meta-analysis comparing the clinical outcomes associated with His⁃Purkinje system pacing(HPSP) versus BIVP in patients with heart failure. There is also a comparison of clinical outcomes of HBP and LBBP in the His⁃Purkinje system. Methods: We searched the Cochrane Library, Embase, and PubMed, for studies published between January 2010 and October 2021, which compared the clinical outcomes associated with HPSP versus BIVP, in patients who underwent CRT. The Pacing threshold，R-wave amplitudes ，QRS duration, New York Heart Association functional ,left ventricular ejection fraction , and LV end-diastolic diameter (LVEDD) of heart failure, at follow-up, were extracted and summarized for meta-analysis. Results: A total of 18 studies17-34 and 1517 patients were included in our analysis. The His-Purkinje system was associated with shorter QRS duration in the CRT population after follow-up compared to BIVP (SMD, -1.17; 95% CI, -1.56 to -0.78; P＜ 0.00001; I²= 74%) . And no statistical difference was verified between HBP and LBBP on QRS duration(SMD, 0.04; 95% CI, -0.32 to 0.40; P = 0.82; I²= 84%) .In the HPSP group, LBBP system was associated with improved LVEF (SMD, 0.67; 95% CI, 0.42 to 0.91; P < 0.00001; I²= 0%) , shorter LVEDD(SMD, 0.59; 95% CI, 0.93 to 0.26; P = 0. 0005; I²= 0%) , and higher New York Heart Association functional class (SMD, -0.65; 95% CI, -0.86 to -0.43; P < 0.00001; I²= 45%) .In terms of pacing threshold and R-wave amplitude clinical outcomes, LBBP has a lower pacing threshold(SMD, 1.25; 95% CI, 1.12 to 1.39; P < 0.00001; I²= 47%) and higher R-wave amplitude(MD, -7.88; 95% CI, -8.46 to -7.31; P < 0.00001; I²= 8%) performance compared to HBP. Conclusion: Our meta-analysis showed that the His-Purkinje system produced higher LVEF, shorter QRS duration, and higher NYHA functional class in the CRT population than the BIVP as observed on follow-up . LBBP has a lower pacing threshold and higher R-wave amplitude.